(untitled) - Tsongas, Paul (New York, 1981)
Contents: Signed by Mr. Tsongas to front end paper; Very Good/Good in Boards; 8vo; Hard cover with Dust Jacket; Alfred A. Knopf; 280 pages; First Edition; Fading to edges of boards; Bump to bottom for edge corner of boards; Text clean and unmarked; Edge wear and rubbing to DJ; Small closed tear to bottom edge of DJ near foot of spine; DJ in arhival mylar jacket.
Keywords: Economic policy,Chinh sách kinh tế; 1981-1993,1981-1993; United States,Hoa Kỳ